Galectin-3 plays a key role in controlling infection by Toxoplasma gondii in human trophoblast cells and human villous explants - Luana Carvalho Luz; Mayara Ribeiro; Samuel Cota Teixeira; Guilherme de Souza; Marina Paschoalino; Daniel Pereira Sousa; Alessandra Monteiro Rosini; Natalia Carine Lima dos Santos; Rafael Martins de Oliveira; Joed Pires de Lima Júnior; Izadora Santos Damasceno; Marcos Paulo Oliveira Almeida; et al. (Frontiers in Cellular and Infection Microbiology)
Galectin-3 (Gal-3) is a β-galactoside-binding lectin expressed in cells of the placental microenvironment. This lectin is involved in various biological processes, such as modulation of the immune system and control of parasitic illness. Toxoplasma gondii infection can lead to congenital transmission and cause miscarriages, prematurity and fetal anomalies. However, little is known about the role of Gal-3 in T. gondii infection in the placental microenvironment. This study aimed to unravel the underlying mechanisms of Gal-3 during T. gondii infection. For this purpose, we promoted the knockdown of Gal-3 expression by using RNA interference (RNAi) in BeWo cells or by using a synthetic inhibitor (GB1107) in human villous explants. We showed that the decreased Gal-3 expression in BeWo cells and human villous explants increases the invasion and proliferation of T. gondii probably by downregulating MIF and IL6 levels, highlighting thus the role of this lectin in modulating the immune response. Collectively, our study reveals Gal-3 as a promising target protein during congenital toxoplasmosis.